DEVELOPING AN EFFECTIVE AND WELCOMING SYLLABUS FOR ENGLISH CLASSES - Kholmurodova , Olima Abdivaliyevna (INTERNATIONAL CONFERENCES, 2023)
In recent days, English language is taught in variety of manners and contexts, namely it is taught by various methods and syllabuses according to the learners’ needs, levels and background country. A course syllabus serves as an important tool for establishing expectations between students and teachers and can be viewed on one level as a contract between the instructor and the student. A well-written syllabus lays out the course’s structure, responds to frequently asked concerns, can help students feel less anxious, and frees up the instructor to focus on teaching.